Influência da descontinuidade serial sobre as regras de montagem em diversidade funcional de algas perifíticas em planície de inundação. - Pereira, Andressa Bichoff (2016)
The distribution of organisms can be influenced by deterministic mechanisms, such as limiting similarity or environmental filters, and can provide divergence or functional convergence. In aquatic environments, such as floodplain river systems, the construction of reservoirs causes the disruption of natural gradients, causing the serial discontinuity, an event that reduces the hydrological connectivity between environments, nutrient cycling, leading to loss of habitat and biological communities. Periphytic algae are important aquatic primary producers and great indicators of environmental conditions. In this way, this study aimed to evaluate the effects of serial discontinuity in a floodplain river system on periphytic algae communities through functional diversity and assembly rules. The hypotheses tested were: along the study area there is an increased functional diversity of periphytic algae; and there is a modification of the functional traits structure of these communities and environmental variables. Expected to occur functional divergence provided by deterministic processes, and that the diversity of functional characteristics increases due to the decrease of the serial discontinuity effect due to propagule input from the tributaries. The samples were taken in November 2014 at 12 points along the Parana River (three points in the Paraná river, six in the tributaries, and three lakes). The periphyton were obtained from scraping petioles of Eichhornia azurea (Sw.) Kunth. Abiotic variables were also evaluated. Life form, adherence strength and form of adhesion to the substrate were the functional characteristics evaluated. The functional diversity was calculated from functional dendrograms and evaluated by null models to test patterns of assembly rules. The results were contrary to expected, and showed functional convergence of periphytic algae along the gradient. There was a fragmentation of the community and the environmental factors in different parts along the study area, which reinforced the importance of local factors in the structuring of these communities. Diatoms were the dominant algae along the gradient. It was possible to relate the traits of life form and form of adhesion with different environmental variables. It was noted the importance of the protected areas, which housing the greatest biodiversity and functional diversity (Parque do Ivinhema) when compared with unprotected environments. In this way, it was demonstrated the importance of maintaining biodiversity as a viable way to ensure the preservation of several ecosystem services over long time.